Subtitusi Pewarna Alami Ekstrak Daun Singkong Pada Pembuatan Telur Gabus Ikan Kembung - Rohimah Siregar; Sri Rafiqoh; Alpina Damanik (Yayasan Literasi Sains Indonesia, 2022)
Cork eggs from mackerel are a snack in the form of long thin strands such as cendol made from tapioca flour, mackerel meat, egg yolks, cheese, salt and water which are fried and have a savory taste and crunchy texture, the addition of natural coloring leaf extract cassava cork egg product from mackerel is intended to increase the nutritional value of cork egg snack from mackerel. The addition of natural dyes from cassava leaf extract, cork egg products from mackerel, is intended not only to beautify the appearance of the product, but also to increase the nutritional value of the cork egg snack from mackerel. This research was conducted by experimental method with complete randomized design one factor, namely the treatment of cassava leaf extract concentration as an additive where the research stage consists of three stages with descriptive data analysis techniques. The results showed that Cork eggs which have the highest antioxidant activity is in treatment A3 with a value of 103.04 µ g/ml.